2017
DOI: 10.1111/1752-1688.12515
|View full text |Cite
|
Sign up to set email alerts
|

Urban Streamflow Response to Imported Water and Water Conservation Policies in Los Angeles, California

Abstract: Los Angeles has a long history of importing water; however, drought, climate change, and environmental mitigation have forced the City to focus on developing more local water sources (target of 50% local supply by 2035). This study aims to improve understanding of water cycling in Los Angeles, including the impacts of imported water and water conservation policies. We evaluate the influence of local water restrictions on discharge records for 12 years in the Ballona Creek (urban) and Topanga Creek (natural) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Urban watersheds in this study have approximately 30% impervious cover, compared to 3% for rural watersheds (Table 1). Therefore, the increased impervious cover of urban watersheds decreases the importance of antecedent soil moisture—which reduces soil drainage—to produce runoff (Manago & Hogue, 2017; Miller & Hess, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Urban watersheds in this study have approximately 30% impervious cover, compared to 3% for rural watersheds (Table 1). Therefore, the increased impervious cover of urban watersheds decreases the importance of antecedent soil moisture—which reduces soil drainage—to produce runoff (Manago & Hogue, 2017; Miller & Hess, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a broad planning process has been examining opportunities for the channelized Los Angeles River to promote economic development and multibenefit uses such as recreation. But water conservation and cuts to imported water reduce treatment plant outflows that constitute a significant percentage of the artificial summer stream flows, would be reduced (Manago and Hogue 2017). In addition, promoting more stormwater infiltration in upstream basins would decrease downstream urban stream flows across the county in most seasons and years (Porse and Pincetl 2018t;Mika et al 2017b).…”
Section: Theme 7: Recognize Tradeoffs In Water Usesmentioning
confidence: 99%
“…In particular, more extreme rainfall events will require infrastructure capable of capturing larger storms to recharge groundwater basins to meet future water supply goals (USBR 2015;. Aquatic habitats and marshlands will be affected by water conservation, imported water losses, and precipitation changes that reduce runoff (Read et al 2018;Thorne et al 2016;Manago and Hogue 2017), themselves artifacts of the current engineered system. Urban trees may suffer in future years without conversion of the tree canopy to low-water species (Pataki et al 2011;Litvak et al 2013Litvak et al , 2017aLitvak et al , 2017bVahmani and Ban-Weiss 2016).…”
Section: Planning For Climate Variability and Changementioning
confidence: 99%
“…The fraction of applied irrigation water that becomes LIRF depends strongly on the irrigation method (e.g., sprinkler vs. drip), timing, and amount (Bijoor et al., 2014; Oad & DiSpigno, 1997), but also can vary with vegetation type, climate conditions, and soil type. Previous work investigating the effects of lawn‐watering restrictions found that streamflow in an urban watershed in Los Angeles, California was seven times larger compared to streamflow in a nearby nonurban watershed before the restrictions were implemented (Manago & Hogue, 2017). Urban streamflow dropped by 70% during the restriction period, while the nonurban watershed experienced no statistically significant changes in streamflow (Manago & Hogue, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work investigating the effects of lawn‐watering restrictions found that streamflow in an urban watershed in Los Angeles, California was seven times larger compared to streamflow in a nearby nonurban watershed before the restrictions were implemented (Manago & Hogue, 2017). Urban streamflow dropped by 70% during the restriction period, while the nonurban watershed experienced no statistically significant changes in streamflow (Manago & Hogue, 2017). Lawn irrigation contributions to streamflow particularly are of interest as the next major focus of municipal water conservation in semi‐arid and arid cities is reduction of urban irrigation (Gober et al., 2016).…”
Section: Introductionmentioning
confidence: 99%